Unified reference system for geometric characteristics dimensional elements of details. Part I. The theory of two dimensions maximum and minimum - V. I. Glukhov; L. G. Varepo (Омский научный вестник)
A unified reference system for geometric characteristics is based on the classification of joints of applied mechanics, in which the class number is determined by the number of degrees of freedom limited by mating elements of parts and has received the short term «informativeness». Different information content of the bases of elements that materialize coordinate systems determines different information content of the coordinate axes – four, two, zero and different information content of design planes – three, two, one. The paper shows that the information content of elements in the functions of auxiliary bases and executive elements determines the number and type of coordinates (linear and angular), with the help of which it is necessary to set their position in the generalized coordinate system of the part. It is shown that the accuracy of coordinating dimensions should be specified by symmetrical tolerances for linear and angular dimensions.